A novel windmill-shaped AIE-active pyrrolopyrrole cyanine: design, synthesis and efficient hydrazine detection. Issue 39 (16th September 2022) - Wang, Lingyun; Xin, Shuqi; Xie, Furong; Ran, Xueguang; Tang, Hao; Cao, Derong
Abstract : A novel windmill-shaped AIE-active PPCy dye was developed and used for efficient hydrazine detection. Abstract : Constructing dyes absorbing and emitting in the near-infrared (NIR) spectral region with aggregation-induced emission (AIE) character is of particular importance but remains challenging. In this work, we developed a windmill-shaped pyrrolopyrrole cyanine (PPCy) by incorporating two triphenylethylene wings at the perimeter of the PPCy core via a thienyl linkage for the first time. The resulting dye (PPCy-TBE) exhibited AIE characteristics, a large Stokes shift (up to 79 nm), and extended absorption and emission maxima at 751 and 825 nm. The results indicated that attaching a rigid AIE rotor at the perimeter of the PPCy core is an efficient and facile strategy to construct an AIE-active PPCy dye. In addition, the windmill-shaped PPCy-TBE showed highly sensitive and selective detection of hydrazine with a limit of detection as low as 0.075 μM, and over 198 nm and 173 nm hypsochromic shifts in the absorption and emission maxima, respectively. The detection mechanism study revealed the combination of acrylonitrile cleavage with B–N bond cleavage by hydrazine to yield much smaller conjugated molecules. Due to its distinct reaction characteristics, the PPCy-TBE -loaded film can conveniently detect hydrazine gas with colorimetric and ratiometric fluorescence "turn on" modes. The hydrazine detection in real samples (tap and lake water) with an excellent recovery rate was also investigated.